Pengaruh Pemasaran Internal dan Kompensasi Terhadap Kepuasan Kerja dan Kinerja Pegawai PLN di Wilayah Sulawesi - Andi Firmansyah; Justine Tanuwijaya (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
This study aims to examine the integration of the relationship between internal marketing dimensions (supportive and participative leadership, training and development, information and communication, and selection and appointments) and compensation with job satisfaction and their impact on the performance of PLN employees in North Sulawesi, Central Sulawesi, and Gorontalo, especially during the COVID-19 post-pandemic. Data was collected from 322 respondents who work at PLN in North Sulawesi, Central Sulawesi, and Gorontalo. The results showed that supportive and participative leadership, information and communication, and compensation significantly positively affected job satisfaction. In contrast, training, development, selection, and appointment had no significant impact on work satisfaction. Job satisfaction has a significant positive effect on employee performance.